The Destructive Bet: Online Gambling's Impact on Individuals and Families in Indonesia - Tifa Noer Amelia; Riyan Anugerah Siregar; Fauzan Azim (Research Synergy Foundation Press, 2026)
Online gambling has emerged as a significant problem in Indonesia, with its widespread accessibility leading to a high potential for addiction and a debt trap. The primary purpose of this research is to analyze the escalating phenomenon of online gambling in Indonesia by employing a crisis management framework to deconstruct its devastating effects on individual and familial stability. This research seeks to move beyond symptom description to identify the structural mechanics of this domestic emergency, ultimately providing a strategic roadmap for moving families from a reactive state of chaos toward resilience and recovery, thereby informing more effective, crisis-oriented therapeutic interventions for affected Indonesian communities. A key finding from a study conducted intensely from January to May 2025, which interviewed and observed four online gambling survivors and their families, was the severe financial consequences. Survivor’s family accrued significant debt from gambling and resorted to high-interest online loans to cover losses, only worsening his situation and attracting debt collectors. To manage this crisis, survivor families adopted various strategies to protect themselves from threats. The survivor itself emphasizes that there is no way to stop gambling unless one fights and commits to escape from the trap. The research applied Mitroff's crisis management theory, noting that while families took proactive steps like securing assets, the emotional and financial wounds caused by the addiction are slow to heal, highlighting the need for further research into the link between online gambling and online loans in Indonesia.